The impact of CSR on corporate reputation perceptions of the public—A configurational multi‐time, multi‐source perspective. (27th September 2018) - Rothenhoefer, Lisa Maria
Abstract: This study investigates the connection between corporate social responsibility (CSR) and corporate reputation among the public using fuzzy set qualitative comparative analysis (fsQCA). To examine complex processes underlying the reactions of this influential stakeholder group, hypotheses are drawn from the category diagnosticity approach. Thereby, a psychological model of perceived (im)morality is transferred to the CSR context. In line with these hypotheses, positive/negative CSR activities influence reputation in the expected directions (H1a, b), while the effects of specific configurations of CSR activities reveal an asymmetry suggesting a negativity bias (H2). Further analyses confirm that positive effects require a consistent positive performance regarding prior reputations (H3a) and the aggregated CSR activities of several previous years (H3b, c). Moreover, the relevant patterns vary between industries (H4). The present study thus contributes to CSR research by investigating a powerful but hitherto understudied stakeholder group through a category diagnosticity lens combined with a configurational approach to analysis.